A higher order PUF complex is central to regulation of C. elegans germline stem cells - Chen Qiu; Sarah L. Crittenden; Brian H. Carrick; Lucas B. Dillard; Stephany J. Costa Dos Santos; Venkata P. Dandey; Robert C. Dutcher; Elizabeth G. Viverette; Robert N. Wine; Jennifer Woodworth; Zachary T. Campbell; Marvin Wickens; et al. (Nature Communications)
Abstract PUF RNA-binding proteins are broadly conserved stem cell regulators. Nematode PUF proteins maintain germline stem cells (GSCs) and, with key partner proteins, repress differentiation mRNAs, including gld-1. Here we report that PUF protein FBF-2 and its partner LST-1 form a ternary complex that represses gld-1 via a pair of adjacent FBF binding elements (FBEs) in its 3′UTR. One LST-1 molecule links two FBF-2 molecules via motifs in the LST-1 intrinsically-disordered region; the gld-1 FBE pair includes a well-established ‘canonical’ FBE and a newly-identified noncanonical FBE. Remarkably, this FBE pair drives both full RNA repression in GSCs and full RNA activation upon differentiation. Discoveries of the LST-1–FBF-2 ternary complex, the gld-1 adjacent FBEs, and their in vivo significance predict an expanded regulatory repertoire of different assemblies of PUF-partner-RNA higher order complexes in nematode GSCs. This also suggests analogous PUF controls may await discovery in other biological contexts and organisms.